Bactericidal and plant defense elicitation activities of Eucalyptus oil decrease the severity of infections by Xylella fastidiosa on almond plants - Montesinos, Laura; Baró, Aina; Gascón, Beatriz; Montesinos, Emilio (Frontiers in Plant Science, 2023)
The activity of Eucalyptus essential oil against eleven strains pertaining to six species of plant pathogenic bacteria was studied using growth inhibition and contact assays. All strains were susceptible to the formulation EGL2, and Xylella fastidiosa subspecies and Xanthomonas fragariae were the most sensitive. The bactericidal effect was strong causing 4.5 to 6.0 log reductions in survival in 30 min at concentrations in the range of 0.75 to 15.0 l/ml depending on the bacteria tested. Transmission electron microscopy of the formulation EGL2 against the three X. fastidiosa subspecies studied allowed the observation of a strong lytic effect on bacterial cells. In addition, the preventive spray application of EGL2 to potted pear plants subsequently inoculated with Erwinia amylovora significantly decreased the severity of infections. Almond plants treated by endotherapy or soil drenching, and then inoculated with X. fastidiosa showed a significant decrease in disease severity as well as in the levels of the pathogen, depending on the strategy used (endotherapy/soil drenching, preventive/curative). The treatment by endotherapy in almond plants induced the expression of several genes involved in plant defense. It was concluded that the reduction of infections by the Eucalyptus oil treatments was due to the combination of its bactericidal and plant defense induction activities.